Pemberdayaan Masyarakat Desa Sukarasa melalui Kolaborasi Lintas Bidang Berbasis Tujuan Pembangunan Berkelanjutan (SDGs) - Febri Fajar Pratama; Syahik Najil Zibran; Syarla Almira; Herawati, Herawati; Mawardah, Mawardah; Rafly Rachman; Haidar (Journal of Empowerment Community, 2026)
Sustainable rural development requires active community participation and cross-sector collaboration to strengthen local social and economic capacity. Sukarasa Village, Salawu District, Tasikmalaya Regency, has considerable untapped potential. This community service program aims to enhance residents' capacity and wellbeing through participatory and collaborative approaches. In 2025, Universitas Perjuangan Tasikmalaya's Community Service Team conducted a Community Service (KKN) initiative emphasizing six key areas: education, health, economy, environment, institutional development, and disaster mitigation. A descriptive participatory approach using Participatory Rural Appraisal (PRA), observation, and interviews was applied to identify community needs. The results indicate improvements in literacy, health awareness, economic independence, environmental concern, and disaster preparedness. Cross-sector collaboration effectively strengthened village capacity and supported the achievement of SDGs 3, 4, 8, and 13.